KONSTRUKSI MUTASI DAERAH RESISTEN RIFAMPIN (GEN rpoB) DARI Mycobacterium leprae PADA PENDERITA LEPRA DI SURABAYA MELALUI ANALISIS GENOM HASIL PCR - E Bimo Aksono H (The East Java Biological Society, 2006)
Rifampin is a key component in the chemoterapeutic regimens used to combat both leprosy and tuberculosis. Owing to exquisite rifampin susceptibility of Mycobacterium leprae, this drug is the backbone of the multidrug therapy currently recommended by WHO for the treatment of leprosy. Resistant mutant are known to arise in leprosy patients receiving rifampin (RIF) monotherapy. The aim of this study was to elucidation of the sequence of the M. leprae rpoB gene permitted identification of mutations associated with rifampin resistance of leprosy patients in Surabaya by genome analysis. M. leprae was detected by nested PCR. In brief, PCR was run with the sense primer rpoBF and anti sense primer rpoBR for 45 cycles. Amplified DNA was analyzed by 3% agarose electrophoresis and the 342 base pairs product was visualized by UV fluorescence after staining with ethidium bromide. PCR product will be purified by phenolchloroform methods and then sequencing directly by ABI PRISM 310. After that sequence data from samples will be analyzed by Genetic Mac ver. 8.0, and comparing with reference data from Gen bank. The result show that only six of 10 samples could be analyzed construct of mutations by Genetic Mac ver 8.0. They have construct no mutation or 100% homology with reference (Z14314 or GI:44382).